PENGARUH CONTEXTUAL TEACHING AND LEARNING TERHADAP KEMAMPUAN KOMUNIKASI DAN DISPOSISI MATEMATIS SISWA SMA NEGERI 04 TEBING TINGGI - Aprillia, Ulfa Dwi; Syahlan, Syahlan; Hasratuddin, Hasratuddin (MAJU : Jurnal Ilmiah Pendidikan Matematika, 2020)
Abstract:Â This study aims to determine whether the CTL learning model is effective against students' mathematical communication disposition and abilities. This research is a quantitative study, the population is students of class X SMA 04 Tebing Tinggi in the academic year 2019/2020. Randomly selected two classes randomly selected namely class X MIA 2 as an experimental class using the CTL learning model and class X MIA 4 as a control class that uses a direct learning model. Data collection methods are the method of observation, tests, and disposition questionnaires. The analysis was performed using the Simple Linear Regression Test. The results of this study indicate that: (1) the influence of CTL on mathematical communication is 91.3%; (2) the effect of CTL on mathematical disposition was 52.7%; (3) communication skills in the control class are better than the experimental class; (4) the mathematical disposition of experimental class students is better than the control class; (5) mathematical disposition has a positive effect on the ability of mathematical communication in the experimental class.Keywords:Â contextual teaching and learning, mathematical disposition, communication ability